Speech Acts in Dialogue Between Characters in the Novel "Banat Ar-Riyadh" by Rajaa Alsanea: Sociolinguistic Study: Al Afal Al Kalamiyyah fi al Hiwar bayna al Shakhsiyyat fi Riwayat Banat al Riyadh li Raja al Sani Dirasah fi Ilm al Lughah al Ijtimai - Achmad Syafri Maulana; Ahmad Fauzi; Mohammad Pribadi (An-Nahdah Al-'Arabiyah, 2026)
This study aims to examine speech acts in the dialogues between characters in Rajaa Alsanea’s novel Banat Ar-Riyadh from a sociolinguistic perspective. The data consist of written utterances from four main characters Qumrah, Sadim, Michelle, and Lamees collected using the listen-and-note technique. A descriptive qualitative approach was applied, employing the act-pair method to identify locutionary, illocutionary, and perlocutionary dimensions, as well as language contact phenomena. The findings reveal two contrasting communication patterns. First, male figures and the older generation tend to dominate directive speech acts by employing Standard Arabic (Fusha) and traditional religious expressions as instruments of social control. Second, urban female characters display micro-resistance through code-switching and code-mixing between Arabic and English, along with the use of contemporary slang (Ammiyah). These linguistic practices function as markers of upper-middle socioeconomic class, as tools to foster solidarity among peers, and as channels for gendered emotional expression. Additionally, dialect stereotypes were observed, indicating sociolinguistic polarization within the speech community.   تهدف هذه الدراسة إلى تحليل أفعال الكلام في الحوارات بين الشخصيات في رواية بنات الرياض للكاتبة رجاء الصانع من منظور سوسيولغوي. تتكون البيانات من الأقوال المكتوبة لأربع شخصيات رئيسية: قُمرة، سديم، ميشيل، ولميس، وقد جُمعت باستخدام تقنية الاستماع والتدوين. أُجري التحليل بطريقة وصفية نوعية من خلال منهج أزواج أفعال الكلام لتحديد أبعاد القول )اللوكسيو، الإلوكسيو، والبيرلوكسيو( ، إضافةً إلى ظواهر التماس اللغوي. أظهرت النتائج وجود نمطين متباينين في التواصل. أولاً، يميل الذكور والجيل الأكبر إلى السيطرة عبر أفعال كلام توجيهية مستخدمين اللغة العربية الفصحى والتعابير الدينية التقليدية كأداة للرقابة الاجتماعية. ثانياً، تُظهر الشخصيات النسائية الحضرية مقاومة دقيقة من خلال التناوب اللغوي والمزج بين العربية والإنجليزية، إلى جانب استخدام العامية المعاصرة (الأمية). وتعمل هذه الممارسات اللغوية كعلامة على الانتماء إلى الطبقة الاجتماعية الوسطى العليا، وكوسيلة لتعزيز التضامن بين الأقران، وكقناة للتعبير العاطفي المرتبط بالهوية الجندرية. كما لوحظت أيضاً صور نمطية لهجاتية تشير إلى وجود استقطاب سوسيولغوي داخل مجتمع الكلام. Penelitian ini bertujuan untuk mengkaji tindak tutur dalam dialog antar tokoh pada novel Banat Ar-Riyadh karya Rajaa Alsanea melalui pendekatan sosiolinguistik. Data berupa tuturan tertulis dari empat tokoh utama Qumrah, Sadim, Michelle, dan Lamees dikumpulkan dengan teknik simak dan catat. Analisis dilakukan secara deskriptif kualitatif menggunakan metode pasangan tindak tutur untuk mengidentifikasi dimensi lokusi, ilokusi, dan perlokusi, serta fenomena kontak bahasa. Hasil penelitian menunjukkan adanya dua pola komunikasi yang kontras. Pertama, tokoh laki-laki dan generasi tua lebih dominan menggunakan tindak tutur direktif dengan bahasa Arab baku (Fusha) dan ungkapan religius tradisional sebagai bentuk kontrol sosial. Kedua, tokoh perempuan urban menampilkan resistensi mikro melalui alih kode dan campur kode antara bahasa Arab dan Inggris, serta penggunaan bahasa gaul (Ammiyah). Pola ini berfungsi sebagai penanda kelas sosial menengah ke atas, sarana mempererat solidaritas, dan medium ekspresi emosional yang berhubungan dengan identitas gender. Selain itu, ditemukan stereotip dialek yang memperlihatkan adanya polarisasi sosiolinguistik di dalam komunitas tutur tersebut.